1985
DOI: 10.1021/bi00333a032
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state carbon-13 nuclear magnetic resonance spectra of acyl .alpha.-chymotrypsin

Abstract: When [13C]carbonyl-enriched p-nitrophenyl 5-n-propyl-2-furoate is incubated with alpha-chymotrypsin, a new peak appears in the 13C NMR spectrum. On the basis of its position and the fact that it is "chased" with unlabeled substrate, we conclude that this new signal is due to the acyl-enzyme intermediate. In spectra taken during steady-state turnover, the acyl-enzyme ester carbonyl 13C chemical shift displays a pH dependence that fits to a titration curve with an apparent pK of 7.1 (0.1). The apparent pK of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The results we have presented here and in previous papers (McWhirter et al, 1985;Wang et al, 1981) permit us a more detailed, albeit still qualitative, picture of the a-chymotrypsin deacylation reaction mechanism. The temperature independence of the 160/180 kie together with our earlier analysis of the nonlinear Arrhenius plots observed by us and others (Baggott & Klapper, 1976;Wang et al, 1981 Laidler, 1967; Click, 1971; Wedler et al, 1975) supports the proposal of at least two active acyl enzyme forms in a temperature-dependent equilibrium.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The results we have presented here and in previous papers (McWhirter et al, 1985;Wang et al, 1981) permit us a more detailed, albeit still qualitative, picture of the a-chymotrypsin deacylation reaction mechanism. The temperature independence of the 160/180 kie together with our earlier analysis of the nonlinear Arrhenius plots observed by us and others (Baggott & Klapper, 1976;Wang et al, 1981 Laidler, 1967; Click, 1971; Wedler et al, 1975) supports the proposal of at least two active acyl enzyme forms in a temperature-dependent equilibrium.…”
Section: Discussionsupporting
confidence: 64%
“…The ethanol transesterification of -chymotrypsinyl 2-furoate has a temperature-independent 160/lsO kie of 1.015 (0.003), from which we conclude that the observed Arrhenius nonlinearity of the transesterification, if not hydrolysis as well, is consistent with a temperature-dependent equilibrium between two acyl enzyme forms that breakdown at different rates. There has been spectroscopic evidence for two forms of the acyl enzyme (MacClement et al, 1981;Shah et al, 1984;McWhirter et al, 1985), but it is not known whether the spectrally and kinetically observed heterogeneities are related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, enzyme intermediates might exist in more than one structural form, or con formational isomers may possibly interconvert. Some experimental evidence has been provided by 13C n m r studies of acyl-chymotrypsin (McClement et al 1981;McWhirter et al 1985).…”
Section: Crystal Structural Analysis Of Catalytic Intermediatesmentioning
confidence: 99%